Pharmacological and Biochemical Characterization of TLQP-21 Activation of a Binding Site on CHO Cells - Molteni, Laura; Rizzi, Laura; Bresciani, Elena; Possenti, Roberta; Petrocchi Passeri, Pamela; Ghè, Corrado; Muccioli, Giampiero; Fehrentz, Jean-Alain; Verdié, Pascal; Martinez, Jean; Omeljaniuk, Robert J.; Biagini, Giuseppe; et al. (Frontiers in Pharmacology, 2017)
VGF is a propeptide of 617 amino acids expressed throughout the central and the peripheral nervous system. VGF and peptides derived from its processing have been found in dense core vesicles and are released from neuronal and neuroendocrine cells via the regulated secretory pathway. Among VGF-derived neuropeptides, TLQP-21 (VGF556-576) has raised a huge interest and is one of most studied. TLQP-21 is a multifunctional neuropeptide involved in the control of several physiological functions, potentially including energy homeostasis, pain modulation, stress responsiveness and reproduction. Although little information is available about its receptor and the intracellular mechanisms mediating its biological effects, recent reports suggest that TLQP-21 may bind to the complement receptors C3aR1 and/or gC1qR. The first aim of this study was to ascertain the existence and nature of TLQP-21 binding sites in CHO cells. Secondly, we endeavored to characterize the ligand binding to these sites by using a small panel of VGF-derived peptides. And finally, we investigated the influence of TLQP-21 on selected intracellular signaling pathways. We report that CHO cells express a single class of saturable and specific binding sites for TLQP-21 with an affinity and capacity of Kd = 0.55 ± 0.05 x 10-9 M and Bmax = 81.7 ± 3.9 fmol/mg protein, respectively. Among the many bioactive products derived from the C-terminal region of VGF that we tested, TLQP-21 was the most potent in stimulating intracellular calcium mobilization in CHO cells; this effect is primarily due to its C-terminal fragment (HFHH-10). TLQP-21 induced rapid and transient dephosphorylation of phospholipase Cγ1 and phospholipase A2. Generation of IP3 and diacylglycerol was crucial for TLQP-21 bioactivity. In conclusion, our results suggest that the receptor stimulated by TLQP-21 belongs to the family of the Gq-coupled receptors, and its activation first increases membrane-lipid derived second messengers which thereby induce the mobilization of Ca2+ from the endoplasmic reticulum followed by a slower store-operated Ca2+ entry from outside the cell.